Interlaboratory evaluation of Mucorales PCR assays for testing serum specimens: A study by the fungal PCR Initiative and the Modimucor study group. (13th June 2020) - Rocchi, S; Scherer, E; Mengoli, C; Alanio, A; Botterel, F; Bougnoux, M E; Bretagne, S; Cogliati, M; Cornu, M; Dalle, F; Damiani, C; Denis, J; et al.
Abstract: Interlaboratory evaluations of Mucorales qPCR assays were developed to assess the reproducibility and performance of methods currently used. The participants comprised 12 laboratories from French university hospitals (nine of them participating in the Modimucor study) and 11 laboratories participating in the Fungal PCR Initiative. For panel 1, three sera were each spiked with DNA from three different species ( Rhizomucor pusillus, Lichtheimia corymbifera, Rhizopus oryzae ). For panel 2, six sera with three concentrations of R. pusillus and L. corymbifera (1, 10, and 100 genomes/ml) were prepared. Each panel included a blind negative-control serum. A form was distributed with each panel to collect results and required technical information, including DNA extraction method, sample volume used, DNA elution volume, qPCR method, qPCR template input volume, qPCR total reaction volume, qPCR platform, and qPCR reagents used. For panel 1, assessing 18 different protocols, qualitative results (positive or negative) were correct in 97% of cases (70/72). A very low interlaboratory variability in Cq values (SD = 1.89 cycles) were observed. For panel 2 assessing 26 different protocols, the detection rates were high (77–100%) for 5/6 of spiked serum. There was a significant association between the qPCR platform and performance. However, certain technical steps and optimal combinations of factors may also impact performance. The good reproducibility and performance demonstrated in this study support the use of Mucorales qPCR as part of the diagnostic strategy for mucormycosis.